2017
DOI: 10.1182/blood-2017-01-761726
|View full text |Cite
|
Sign up to set email alerts
|

Acquired mutations associated with ibrutinib resistance in Waldenström macroglobulinemia

Abstract: Key Points BTKCys481 mutations, including multiple mutated variants within individual patients are common in ibrutinib-progressing WM patients. BTKCys481 mutations were associated with mutated CXCR4 in WM patients progressing on ibrutinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 25 publications
3
88
1
1
Order By: Relevance
“…This expands upon prior studies demonstrating CXCR4 mutations confer both in vitro and clinical resistance to ibrutinib . Acquired BTK C481S mutations are also strongly associated with CXCR4 mutations in the development of ibrutinib resistance . Importantly, 80% of patients deemed to be ibrutinib nonresponders in our cohort harbored a CXCR4 mutation, and all discontinued ibrutinib within 6 months of treatment initiation.…”
Section: Discussionsupporting
confidence: 79%
“…This expands upon prior studies demonstrating CXCR4 mutations confer both in vitro and clinical resistance to ibrutinib . Acquired BTK C481S mutations are also strongly associated with CXCR4 mutations in the development of ibrutinib resistance . Importantly, 80% of patients deemed to be ibrutinib nonresponders in our cohort harbored a CXCR4 mutation, and all discontinued ibrutinib within 6 months of treatment initiation.…”
Section: Discussionsupporting
confidence: 79%
“…Supporting the conclusion that BTK and PLCG2 mutations are not necessary for ibrutinib resistance, studies in other B cell lymphomas have also identified resistance mechanisms that do not involve mutations in BTK or PLCG2. In Waldenstrom’s macroglobulinemia and mantle cell lymphoma (MCL), mutations in CARD11 have been reported in ibrutinib-resistant disease and some of these mutations can block sensitivity of MCL cell lines to ibrutinib in vitro [30, 31]. Activating mutations in CARD11 also predict primary resistance to ibrutinib in follicular lymphoma [32] and diffuse large B cell lymphoma [33].…”
Section: Btk and Plcg2 Mutations Are Not Necessary For Acquired Resismentioning
confidence: 99%
“…Whilst TP53 may not be the contributing factor to therapy resistance, it may be an indicator of genomic instability. This suggests that additional mutation testing may be required for BTK and PLCG2 , both of which have been shown to drive resistance to BTKi therapy in WM (Xu et al , ).…”
Section: Summary Of Wm Patients (N = 14) and Samples (N = 58)mentioning
confidence: 99%